Correlates of intimate partner violence among HIV-positive women in southwest Nigeria. (March 2015) - Ezebuka, O; Sam-Agudu, N; Erekaha, S; Dairo, M
Abstract: Background: The prevalence of domestic violence among Nigerian women increased from 21% in 2011 to 30% in 2013, with an estimated two-thirds of these women experiencing violence from a male intimate partner. Previous studies have found a correlation between HIV-positive status and domestic violence in Nigerian women. In this study, we aimed to identify different forms of, and factors associated with, intimate partner violence (IPV) among women living with HIV in southwestern Nigeria. Methods: We conducted a cross-sectional survey at a tertiary health facility that cares for more than 1500 women living with HIV. The research team, including a facility-based counsellor, used a structured questionnaire to collect sociodemographic and intimate relationship data from participants. Information about IPV before and after women disclosed their HIV status to partners was collected. IPV forms were categorised as physical, sexual, and psychological according to WHO Domestic Violence definitions. Characteristics of respondents who reported IPV were compared with those for women who did not. We used Z tests and χ 2 tests to compare dependent and independent samples, respectively, and we used multivariate logistic regression to identify factors independently associated with IPV. Findings: Between May 1 and May 30, 2013, we interviewed 328 women, which represents about 22% of HIV-positive women attending the facility. Mean age was 33·1 years (SD 0·73). Most women (226 [68·9%]) knew their partner's HIV status for the previous 12 months; 32·3% (106) had an HIV-positive partner, and 36·6% (120) had a partner who was HIV-negative. Over a third of women (115 [35·1%]) had experienced any form of IPV. Psychological violence (62/115 [53·9%]) was the most common type of violence reported by respondents, followed by physical violence (40/115 [34·8%]) and sexual violence (39 [33·9%]). There was a 62·8% (206/328) HIV disclosure rate to partners; of these women, 79 (38·3%) reported experiencing pre-disclosure IPV, with 40 (50·6%) experiencing physical violence, 39 (49·4%) sexual violence and 62 (78·5%) psychological violence. However, a higher proportion of women (115/206 [55·8%]) experienced IPV post-disclosure compared with pre-disclosure IPV (p=0·0004), with 58 (50·4%) of these women experiencing physical violence, 71 (61·7%) sexual violence, and 113 (98·2%) psychological violence. Correlates for post-disclosure IPV were having an HIV-positive partner (p<0·0001), partner aged 40 years or more (p<0·0001), partner's education being of low level (that is, no formal/primary education) (p=0·004), alcohol intake by partner (p=0·001), cohabitation (p=0·002), marriage (p=0·03), and having more than one sexual partner (for male partner p=0·02, for respondent p<0·0001). Interpretation: HIV-status disclosure increases the risk of IPV in women living with HIV. Post-disclosure IPV rate was significantly higher than for pre-disclosure, and was greater than the national domestic violence rate in Nigeria. Post-disclosure IPV rate strongly correlated with HIV-positive status of the male partner and multiplicity of sexual partners. This might predispose partnered women to non-disclosure, which in turn could decrease uptake or access to HIV care, and increase rates of HIV transmission to more partners and to children. Fear of IPV, and resultant non-disclosure have dire consequences for positive living among women/mothers, and for HIV control in general. We recommend strengthening of community-wide IPV education with a special focus on HIV-positive male partners in high-burden areas. Couples' HIV testing and counselling should also be encouraged to minimise harm to women living with HIV. Funding: None.